Anthropostratigraphy: New lithological units of the Quaternary controlled by human activity - Colombo, F.; Riba, O.; Reguant, S.; Virgili, C.; Rivero, L. (Journal of Iberian Geology, 2013)
Many areas around the world such as the Mediterranean region have been inhabited without interruption for thousands of years. This is the case of the city of Barcelona (Spain), where remains of human settlements dating from pre-Roman times until the present have been found. A detailed geological mapping of the area occupied by the city of Barcelona raises a number of questions about the Holocene stratigraphy affected by human activity. In the old urban and surrounding areas most of the sedimentary deposits accumulated during settlement result from human interactions. Thus, new anthropostratigraphic units are proposed. The sedimentary deposits and the infill of rock excavations due to human presence may be divided into three categories: Natural lithoanthropogenic units (NAU) when their formation is not directly affected by anthropogenic activity but these contain artefacts of human origin. Induced lithoanthropogenic units (IAU) when natural processes together with human actions produce sedimentation or erosion due to natural phenomena; Constructed lithoanthropogenic units (CAU) when sedimentary accumulations and sharp contacts result from direct human activity.